Social embeddedness as a mechanism for linking social cohesion to well-being among older adults: moderating effect of gender - Momtaz, Yadollah Abolfathi; Haron, Sharifah Azizah; Ibrahim, Rahimah; Tengku Abdul Hamid, Tengku Aizan (Dove Medical Press, 2014)
Background: The positive effect of social cohesion on well-being in older adults has been well documented. However, relatively few studies have attempted to understand the mechanisms by which social cohesion influences well-being. The main aim of the current study is to identify social pathways in which social cohesion may contribute to well-being. Methods: The data for this study (taken from 1,880 older adults, aged 60 years and older) were drawn from a national survey conducted during 2008–2009. The survey employed a two-stage stratified sampling process for data collection. Structural equation modeling was used to test mediating and moderating analyses. Results: The proposed model documented a good fit to the data (GFI =98; CFI =0.99; RMSEA =0.04). The findings from bootstrap analysis and the Sobel test revealed that the impact of social cohesion on well-being is significantly mediated by social embeddedness (Z=5.62; P<0.001). Finally, the results of a multigroup analysis test showed that social cohesion influences well-being through the social embeddedness mechanism somewhat differently for older men than women. Conclusion: The findings of this study, in addition to supporting the importance of neighborhood social cohesion for the well-being of older adults, also provide evidence that the impact of social cohesion towards well-being is mediated through the mechanism of social embeddedness.